Evaluation of a sterile surgical skin marker to indicate the optimal vein for venepuncture in the blood donation setting. Issue 5 (2nd March 2020) - Bell, Barbara; O'Donovan, Justine; Wright, Stephen T.; Gemelli, Carley N.; Knight, Elizabeth; Hirani, Rena
Abstract : Background and objectives: Phlebotomy is a central task for blood donation; however, not all blood donors have veins that are easy to see or feel. This study aimed to determine whether use of a surgical skin marker to highlight the donors' vein location and direction prior to venepuncture increased blood donation success. Methods: All blood donors who participated in this study were eligible to donate according to Australian guidelines. Ten donor centres with phlebotomy success rates <95% were selected. A randomized cluster trial design assigned five sites to test the skin marking device and five sites as controls. Single‐use sterile Gentian violet skin marker pens were used to mark donors' veins. Phlebotomy site skin bacterial load after using the skin marking device was tested on a subset of 100 donors. Phlebotomy success rates and donor adverse events were recorded. Results: Of the control donors, 6993 had successful phlebotomies and 225 failed. Of the skin marker donors, 6998 had successful phlebotomies and 248 failed. No statistically significant differences in phlebotomy success were found between the two groups (OR: 0·91, 96·4% CI [96·0, 96·8], P ‐value 0·348). Conclusion: The use of skin marker pens did not increase overall phlebotomy success rate. There was no increase in phlebotomy site skin bacterial load, and amendments to standard skin disinfection techniques were not required. Blood donors were not concerned about the pen mark on their arms. Generally, staff indicated that the markers may be valuable to assist with phlebotomies for donors with difficult or deep veins.